2021
DOI: 10.3390/ijms22041618
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoa Transcriptional Response and Alterations in PL Proteins Properties after Exposure of Mytilus galloprovincialis to Mercury

Abstract: Mercury (Hg) is an environmental pollutant that impacts human and ecosystem health. In our previous works, we reported alterations in the properties of Mytilus galloprovincialis protamine-like (PL) proteins after 24 h of exposure to subtoxic doses of toxic metals such as copper and cadmium. The present work aims to assess the effects of 24 h of exposure to 1, 10, and 100 pM HgCl2 on spermatozoa and PL proteins of Mytilus galloprovincialis. Inductively coupled plasma–mass spectrometry indicated accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…The graph describing the results obtained indicated that the absorbance at 420 nm of the PL solution slightly increased as the concentration of HgCl 2 incremented differently from that of Bovine Serum Albumin (BSA) ( Figure 1 a). This result suggests the possible formation of protein aggregates, corroborating that already obtained in Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) ( Figure 1 b) [ 28 ], in which additional protein bands with reduced mobility were observed in the samples of PL proteins extracted from mussels exposed to 1, 10 and 100-pM HgCl 2 .…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The graph describing the results obtained indicated that the absorbance at 420 nm of the PL solution slightly increased as the concentration of HgCl 2 incremented differently from that of Bovine Serum Albumin (BSA) ( Figure 1 a). This result suggests the possible formation of protein aggregates, corroborating that already obtained in Sodium Dodecyl Sulphate-Polyacrylamide Gel Electrophoresis (SDS-PAGE) ( Figure 1 b) [ 28 ], in which additional protein bands with reduced mobility were observed in the samples of PL proteins extracted from mussels exposed to 1, 10 and 100-pM HgCl 2 .…”
Section: Resultssupporting
confidence: 89%
“…In order to identify any changes in the PL protein electrophoretic mobility after the exposure of mussels to HgCl 2 , we performed an electrophoretic analysis by SDS-PAGE, maintaining the same final percentage of acrylamide described by Lettieri et al 2021 [ 28 ] but changing the Acrylamide-Bisacrylamide ratio (29:1) in order to obtain an higher resolution of the protein bands. In these conditions, the electrophoretic pattern by SDS-PAGE of the PLII and PLIII proteins ( Figure 3 ) showed that after the exposure of mussels to 10-pM HgCl 2 ( Figure 3 b, lane 3), the band corresponding to the PLII protein did not seem to appear on the gel in the position observed in the control ( Figure 3 b, lane 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations